2020
DOI: 10.1186/s40816-020-0152-9
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of antioxidant, anti-hemolytic, cytotoxic effects and anti-bacterial activity of selected mangrove plants (Bruguiera gymnorrhiza and Heritiera littoralis) in Bangladesh

Abstract: Objectives: In this present study, antioxidant, anti-hemolytic, cytotoxic and anti-bacterial activities derived from methanol extracts of Bruguiera gymnorrhiza and Heritiera littoralis were investigated in order to determine their medicinal activities.Materials and methods: Folin-Ciocalteu reagent method and aluminum chloride methods were used to determine the mangroves' total phenolics and total flavonoid content, respectively. Antioxidant capacity was assessed via the following methods: 1,1-diphenyl-2-picryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 71 publications
1
24
0
3
Order By: Relevance
“…The thrombolytic potential of T. foenum-graecum extract is an important finding, which may have implications in cardiovascular health, especially in atherothrombotic patients. These results are in agreement with Ktari et al [ 62 ], which also reported cytotoxicity of T. foenum-graecum extract, and no hemolytic activity was reported against bovine RBCs.…”
Section: Discussionsupporting
confidence: 93%
“…The thrombolytic potential of T. foenum-graecum extract is an important finding, which may have implications in cardiovascular health, especially in atherothrombotic patients. These results are in agreement with Ktari et al [ 62 ], which also reported cytotoxicity of T. foenum-graecum extract, and no hemolytic activity was reported against bovine RBCs.…”
Section: Discussionsupporting
confidence: 93%
“…This implies that Am-AgNPs is best used at lower concentration because a high concentration as used in this study is toxic to RBC membrane (Raja et al 2016;Hamouda et al 2019). Anti-haemolytic activity of plant extract has been shown to be related to the constituent antioxidant agents such as polyphenolic compound (Ramchoun et al 2015;Karim et. 2020).…”
Section: Anti-haemolytic Effects Of Aqueous Leaf Extract Of a Muricat...mentioning
confidence: 96%
“…It is interesting to highlight that the phenolic content was quantified in different amount from the same type of extract by different studies. For instance, a study conducted by Haq et al quantified 178.73 ± 0.23 mg GAE/g of phenolic content from the methanolic leaf sample [13], while Karim et al (2020) reported a phenolic content equivalent of 58.917 ± 0.601 mg gallic acid/g [25] and Banerjee et al (2008, reported a much lower quantity of 8.25 ± 0.31 mg GAE/g from the same extract (i.e., methanolic leaf) [12]. Herein, our results showed that the methanolic leaf sample yielded a lower amount (30.26±0.25 mg GAE/g) compared to the studies of Haq et al, (2011) and Karim et al, (2020) but higher than Banerjee et al, (2008).…”
Section: Bioactive Compoundsmentioning
confidence: 99%